Chamas for Change: an integrated community-based strategy of peer support in pregnancy and infancy in Kenya. (March 2015) - Christoffersen-Deb, A; Ruhl, L; Elung'at, J; Atieno, M; Snelgrove, J; Songok, J
Abstract: Background: Many women and children face the challenges of pregnancy and infancy without supportive relationships at home or in the community. To address this problem, the Academic Model Providing Access to Healthcare (AMPATH), in partnership with the Government of Kenya, launched Chama cha MamaToto, a peer-support model that groups women together at the start of their pregnancies. Central to our approach is the integration of microfinance into a group model that focuses on health education and relationship strengthening using a social fundraising platform well known to women: chamas. Chamas are effective networks through which women can meet regularly outside the home and pool resources. Using this existing cultural script, we developed these mother-child investment clubs in a rural district. Through their operation as a "table banking system", members become shareholders in each other's futures, not only through the disbursement of loans, but also by keeping each other accountable to healthy practices for themselves and their children. The meetings provide opportunities for community health workers (CHWs) to efficiently disseminate health information, organise referrals, and build relationships with women and infants. Methods: In 2012, 32 Government of Kenya CHWs recruited more than 400 pregnant and breastfeeding women to 16 chamas in Bunyala subcounty, Kenya. These groups met fortnightly for 12 months. On joining, women pledged to participate for 1 year and to uphold the goals of the chama: support each other, attend prenatal care, deliver in a health facility, breastfeed exclusively for 6 months, adopt long-term family planning, save money, and become entrepreneurs. To evaluate the effect, acceptability, and sustainability of chamas, we compared data from a prospective cohort of women in chamas with a group of controls who did not belong to a chama, matched for age, parity, and location of prenatal care. Findings: We analysed data for 222 chama women and 115 controls, and found that compared with controls, women in chamas were 73% more likely to attend four recommended prenatal visits (64% vs 37%, p<0·001), 67% more likely to give birth in a health facility (84% vs 50%, p<0·001), 75% more likely to breastfeed exclusively to 6 months (82% vs 47%, p<0·001), and 98% more likely to receive the recommended homevisit from a CHW within 48h of birth (76% vs 38%, p<0·001). Furthermore, women in chamas were less likely to have a stillbirth or newborn death (2·4% vs 5·2%, p=0·083). Interpretation: Chamas can be tailored to increase the uptake of health services in pregnancy and infancy. Chamas for Change is designed to enable populations to sustain beneficial health effects beyond the funding period by equipping women with the peer and financial supports necessary to sustain change. As the programme enters its third year, we propose a cluster randomised trial of chamas across three counties and one million people as a population-wide strategy to rapidly and sustainably achieve health and gender equity outcomes. Funding: We received funding from Saving Lives at Birth and USAID PEPFAR.